Syzygium cumini anthocyanins: recent advances in biological activities, extraction, stability, characterisation and utilisation in food systems - Darshanjot Kaur; Basharat Yousuf; Ovais Shafiq Qadri (Food Production, Processing and Nutrition, 2024)
Abstract Syzygium cumini anthocyanins have become an area of great interest as biocolourants in the food industry. These anthocyanins impart a deep colour over a suitable pH range due to the high amount of anthocyanin content compared to other natural sources. An important aspect is selecting an appropriate technique where a high yield of anthocyanins can be obtained from the pulp of S. cumini fruit. Among various extraction techniques, ionic/ organic solvents and ultrasonication are the most employed methods due to their efficiency. These green extraction techniques are advantageous over conventional techniques due to the high recovery of anthocyanins utilising much less solvent in a shorter duration with minimal degradation. Despite that, the utilisation of recovered anthocyanins is restricted to mainly acidic (dairy) products due to their instability towards environmental parameters such as pH, light, temperature, enzymes, and metal complexes. Additionally, according to experimental studies, co-pigmentation and acylation could improve anthocyanins’ stability. Being one of the most potential sources of anthocyanins, S. cumini fruits can be exploited for extraction of this biocolourant. However, there is discontinuity in the research between extraction and utilization of S. cumini anthocyanins as is evident from the literature survey. In this review we have summarized the research advances being executed to enhance the extraction and utilization of S. cumini anthocyanins using green or novel techniques and a brief account of stability analysis, characterization, and utilization. Graphical Abstract